2020
DOI: 10.31661/gmj.v9i0.1862
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Health Literacy, a Strategy for the Challenges of Sexual Life of Infertile Women: A Qualitative Study

Abstract: Background: Sexual health literacy enables an understanding and application of sexual health information and has benefits beyond health. Health literacy is an important element for achieving cognitive skills in health promotion. One of the most important problems in sexual health and sexual function in women is infertility. This study aims to explore the dimensions of sexual health literacy among women with infertility. Materials and Methods: In this qualitative study, a total of 18 individual interviews with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…Health literacy is an important subject across all specialities, including both infectious disease and sexual health. Whilst not a sexually transmitted infection, PEMs created about monkeypox rely on patients having an ‘ability to understand sexual health information and application of that information’ to be able to make informed choices with regard to sex and safe sex practices, also defined by the WHO as sexual health literacy [ 24 ]. Electronic health literacy is also crucial in our increasingly technologized world, and refers to the processing and understanding of health information from electronic sources.…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy is an important subject across all specialities, including both infectious disease and sexual health. Whilst not a sexually transmitted infection, PEMs created about monkeypox rely on patients having an ‘ability to understand sexual health information and application of that information’ to be able to make informed choices with regard to sex and safe sex practices, also defined by the WHO as sexual health literacy [ 24 ]. Electronic health literacy is also crucial in our increasingly technologized world, and refers to the processing and understanding of health information from electronic sources.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the tool developed by Dabiri et al suggested a four-factor structure (reading and understanding, access, information evaluation, decision-making, and information application) to measure sexual health literacy [12]; While the tool designed by Karimi et al [24]. introduced a structure of seven factors (access, reading, understanding, evaluation, [26]. On the other hand, the results of exploratory factor analysis showed that one item from "the evaluation and analysis" factor (I can properly transfer my learned knowledge about sexual health to others) was omitted due to insufficient factor loading (item number 29) because it was largely associated with communication skills which was a separate area of health literacy [27].…”
Section: Discussionmentioning
confidence: 99%
“…We also know that people must access specific resources and databases to be sexually literate. Rakhshaee et al showed that providing "the information needs" for women's sexual health was the most important dimension of sexual health literacy for them [26]; therefore, considering the low number of these sources and databases for women in Iran [3], this finding indicated the high need for women to increase access to sexual health information. In general, the present study examined and confirmed the variability of the factors of this questionnaire in the female population and showed that the factors could be variable if used in different populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the access and quality of sexual health services received have been one of the main challenges of delivering such services in Iran’s PHC system [ 17 , 18 ]. Given sexual health services are one the significant factors of providing and promoting SHL, and that SHL is a concept that is affected by contextual factors, society’s socio-cultural structure, and the target audiences’ traits [ 1 , 5 , 19 ], thus, the current study was conducted to describe the perceptions and experiences of health care providers and recipients for establishing the sexual health literacy services in health care services in future.…”
Section: Introductionmentioning
confidence: 99%